(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
The objectives of this study is to evaluate the effectiveness of excision of a part of meat surface versus swabbing as methods for the assessment of bacterial load of bovine carcasses and also to recommend a harmonized methodology to be used in monitoring and improving the safety and quality of meat as for as bacterial load of carcasses at slaughterhouses in Khartoum state. Swabbing and Excision samples were taken from three sites of bovine carcasses which are flank, brisket and neck after the stage of carcasses evisceration. A total of 240 samples were taken from 40 bovine carcasses (three swabs samples and three excision samples from each carcass), all collected samples were processed for viable counts using miles and misra method. Mean viable counts ranged from 3.19to3.5 cm -2 for bovine carcasses and excision method generally recovered bacteria more than swabbing method, the mean viable counts of swabbing from flank, brisket and neck are 3.2125, 3.1925, and 3.225 respectively. And the mean viable counts of excision from these sites are 3.48, 3.4525 and 3.505, respectively. There is significant difference (P-value < 0.05) between swabbing and excision sampling methods in the flank, brisket and neck, P-value is 0.003786, 0.005563, and 0.00266, respectively. Swabbing viable counts at the different sites revealed there is no significant difference (P-value > 0.05) between the different sites and excision viable counts at the different sites also revealed there is no significant difference (P-value > 0.05) between the different sites, P-value is 0.965701 and 0.229126, respectively. The results showed that excision method generally recovered bacteria more than swabbing method; therefore, excision method proved to be the most effective technique for bacterial recovery from bovine carcasses at slaughterhouses in Khartoum stat